Nascent entrepreneurship : A bibliometric analysis and systematic literature review - Aranyossy, Márta; Szabó, Krisztofer (Vezetéstudomány, 2022)
Nascent entrepreneurship studies contribute to the understanding of entrepreneurial intention of individuals which in turn has significant effects on economic growth and labour markets. This paper presents a systematic literature review of nascent entrepreneurship research focused articles published between 2000 and 2020 based on bibliometric analysis and quantitative and qualitative text analysis. A corpus of 257 journal articles was assembled to provide insights on the most important themes and trends in the research stream as well as focusing on the most prominent journal outlets and influential authors. In-depth examination of the 30 most cited articles serves as a basis for proposed systematisation of factors influencing nascent entrepreneurial intentions. A summary of promising research directions and emerging themes is also presented.